SQL for Dummies 5th Edition - Taylor, Allen G. (Wiley Publishing, 2011)
Relational database management systems are vital to many organizations. People often think that creating and maintaining these systems are extremely complex activities — the domain of database gurus who possess enlightenment beyond that of ordinary mortals. This book sweeps away the database mystique. In this book, you Get to the roots of databases. Find out how a DBMS is structured. Discover the major functional components of SQL. Build a database. Protect a database from harm. Operate on database data. Determine how to get the information you want out of a database. The purpose of this book is to help you build relational databases and get valuable information out of them by using SQL. SQL is the international standard language used around the world to create and maintain relational databases. This edition covers the latest version of the standard, SQL:2003. This book doesn’t tell you how to design a database (I do that in Database Development For Dummies, also published by Wiley Publishing, Inc.). Here I assume that you or somebody else has already created a valid design. I then illustrate how you implement that design by using SQL. If you suspect that you don’t have a good database design, by all means, fix your design before you try to build the database. The earlier you detect and correct problems in a development project, the cheaper the corrections will be.